Bidirectional Electron Transfer in the Reaction Centre of Photosystem I - Santabarbara, Stefano; Galuppini, Luca; Casazza, Anna Paola (Journal of integrative plant biology, 2010)
In the past decade light-induced electron transfer reactions in photosystem I have been the subject of intensive investigations that have led to the elucidation of some unique characteristics, the most striking of which is the existence of two parallel, functional, redox active cofactors chains. This process is generally referred to as bidirectional electron transfer. Here we present a review of the principal evidences that have led to the uncovering of bidirectionality in the reaction centre of photosystem I. A special focus is dedicated to the results obtained combining time-resolved spectroscopic techniques, either difference absorption or electron paramagnetic resonance, with molecular genetics, which allows, through modification of the binding of redox active cofactors with the reaction centre subunits, an effect on their physical-chemical properties.